2010
DOI: 10.1002/biot.201000095
|View full text |Cite
|
Sign up to set email alerts
|

CHO‐K1 host cells adapted to growth in glutamine‐free medium by FACS‐assisted evolution

Abstract: During the process of recombinant cell line optimisation for production of biopharmaceuticals, multiple cellular properties like robustness against stress, the attainment of high cell concentrations and maintenance of high viability must be considered to maximize protein yield. To improve growth and viability, glutamine is supplemented as an alternative energy source for rapidly dividing cells that oxidize glucose inefficiently. However, the resulting by‐product ammonia is toxic at high concentrations and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…The decomposition rate is dependent on the pH [81,82], temperature [80] and phosphate concentration [83]. For example, Ozturk and Palsson [81] showed that the actual uptake of glutamine in hybridoma cell culture was three-fold lower than the apparent uptake.Ammonium that is released via glutaminolysis and glutamine decomposition is a toxic by-product in mammalian cell cultures [84]. Ammonium can accumulate to levels up to 2-10 mM in batch cultures [11], and can negatively affect cell growth [85][86][87][88], protein production [89] and protein glycosylation [9,[90][91][92][93].…”
Section: Glutaminolysis and Tca Cyclementioning
confidence: 99%
“…The decomposition rate is dependent on the pH [81,82], temperature [80] and phosphate concentration [83]. For example, Ozturk and Palsson [81] showed that the actual uptake of glutamine in hybridoma cell culture was three-fold lower than the apparent uptake.Ammonium that is released via glutaminolysis and glutamine decomposition is a toxic by-product in mammalian cell cultures [84]. Ammonium can accumulate to levels up to 2-10 mM in batch cultures [11], and can negatively affect cell growth [85][86][87][88], protein production [89] and protein glycosylation [9,[90][91][92][93].…”
Section: Glutaminolysis and Tca Cyclementioning
confidence: 99%
“…CHO-K1 suspension cell lines adapted to growth in glutamine free media (Bort et al, 2010) were cultivated in 500 ml spinner flasks using CD CHO media (Gibco, Invitrogen, Carlsbad, CA, USA) under 7% CO 2 and incubated at 37 °C with constant stirring at 50 rpm. Viability and cell counts were measured on a Vi-Cell analyzer (Beckman Coulter Inc., Fullerton, CA) based on the trypan-blue dye exclusion method.…”
Section: Methodsmentioning
confidence: 99%
“…CHO-K1 cells that can grow in the glutamine-free medium were selected using fluorescence-activated cell sorting FACS or magnetic activated cell sorting [87]. The selected cells showed similar or even better growth and viability profiles compared with parental CHO-K1 cells.…”
Section: Other Strategies To Reduce Ammonia Formationmentioning
confidence: 99%